The Microtubule-Depolymerizing Kinesin-13 Klp10A Is Enriched in the Transition Zone of the Ciliary Structures of Drosophila melanogaster - Persico, Veronica; Callaini, Giuliano; Riparbelli, Maria Giovanna (Frontiers in Cell and Developmental Biology, 2019)
The precursor of the flagellar axoneme is already present in the primary spermatocytes of Drosophila melanogaster. During spermatogenesis each primary spermatocyte shows a centriole pair that moves to the cell membrane and organizes an axoneme-based structure, the cilium-like region (CLR). The CLRs persist through the meiotic divisions and are inherited by young spermatids. During spermatid differentiation the ciliary caps elongate giving rise to the sperm axoneme. Mutations in Klp10A, a kinesin-13 of Drosophila, results in defects of centriole/CLR organization in spermatocytes and of ciliary cap assembly in elongating spermatids. Reduced Klp10A expression also results in strong structural defects of sensory type I neurons. We show, here, that this protein displays a peculiar localization during male gametogenesis. The Klp10A signal is first detected at the distal ends of the centrioles when they dock to the plasma membrane of young primary spermatocytes. At the onset of the first meiotic prometaphase, when the CLRs reach their full size, Klp10A is enriched in a distinct narrow area at the distal end of the centrioles and persists in elongating spermatids at the base of the ciliary cap. We conclude that Klp10A could be a core component of the ciliary transition zone in Drosophila.